Determinants of Intellectual Capital Disclosure in Non-Vocational Higher Education in Indonesia - Indah Cahyani Gobel; Ahmad Juanda; Ihyaul Ulum; Mudrifah Mudrifah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research aims: This study aims to how intellectual capital (IC) disclosure has been carried out by Indonesian higher education institutions (HEI). In addition, this study examines the determinants of IC disclosure, namely age, size and accreditation status of HEI.Design/Methodology/Approach: The IC components used in this study refers to Ulum (2019), which modified the research from Leitner and Karl-Heinz (2002). This modification refers to the Study Program Accreditation Instrument (IAPS) 4.0 which has been regulated by the National Accreditation Board for Higher Education. The hypotheses test is conducted using SEM PLS.Research findings: The test results show that the age, size and accreditation status variables have a significant effect on intellectual capital disclosure (ICD).Theoretical contribution/ Originality: This study examines the IC disclosure with IAPS 4.0 that has just been applied in Indonesia.Practitioner/Policy implication: The study results provide an overview of the factors that drive IC disclosure in Indonesian HEI.Research limitation/Implication: This study only involved 86 large Indonesian non-vocational HEI.